IMPROVING STUDENTS' LISTENING SKILL BY USING ENGLSIH SONG - INDRA PURNAWAN PANJAITAN (JURNAL ILMIAH MAKSITEK, 2018)
This reaserch aimed to improve students’ listening skill by using English song. The other hand this reaserch aimed to know the students attitudes of using English songs in listening skill. The reason of choosing this topic is based on the problem that faced by the students when learning Listening. The method was a classroom action research that consisted of pre-test, two cycles, and post-test. Each cycle consisted of four steps: planning, action, evaluation, and reflection. The subject was the second year students of SMA Muhammadiyah 09 Kualuh Hulu Kabupaten Labuhanbatu Utara that consisted of 20 students. The instrument was a test and analyzed by mean score formula. The result showed that in pre-test, the students got mean score 43,75 (low). In cycle 1, they got 48,6 (low). In cycle 2, they got 60,5 (moderate). In post-test, they got 75,8 (good). So, it can be concluded that the use of songs improved the second year students’ listening skill at SMA Muhammadiyah 09 Kulauh Hulu Kabupaten Labuhanbatu Utara.